Mapping Abandoned Cultivated Land in China: Implications for Grain Yield Improvement - Guanghui Jiang; Wenqiu Ma; Yuling Li; Dingyang Zhou; Tao Zhou (Applied Sciences)
The abandonment of cultivated land has profoundly affected the agroecological landscape, national food security, and farmer livelihoods, especially in China. Based on land use change survey data and national geoinformation survey data, this paper identified the distribution of abandoned cultivated land and analyzed the overall characteristics and spatial differentiation patterns of abandoned cultivated land in China. The results showed that: (1) In 2017, the abandoned area of cultivated land in China was approximately 9.10 million hectares, with an overall abandoned rate of approximately 5.57%. (2) The distribution of abandoned land in China had obvious spatial differences, and the trend of the area of abandoned land had an “inverted U” shape from east to west. (3) The pattern of abandonment showed a trend of spreading from a scattered distribution to a concentrated and continuous expansion from the edges of large cities and remote rural areas to the main grain-producing regions of fertile cultivated land. (4) The cultivated land abandonment has a great impact on grain production capacity, and there are differences among provinces. In 2017, China lost 40.89 million tons of grain yield due to cultivated land abandonment, accounting for 6.48% of the total grain yield, and the loss of potential grain yield reached 254.45 million tons. The cultivated land abandonment was driven not only by social effects under the dual structure of urban and rural areas but also by the rational choices of farmers under the overall balance of national policy, cultivated land income, and opportunity cost under the framework of urbanization. In the future, policy tools such as fallowing, land conversion, high farmland construction standards, and subsidies should be used to implement differentiated land use policies and optimize the spatial pattern of cultivated land use.